EMBRIOGENESIS SOMATIK ANGGREK BULAN Phalaenopsis amabilis (L.) Bl: STRUKTUR DAN POLA PERKEMBANGAN - Edy Setiti Wida Utami; Issirep Soemardi; Taryono Taryono; Endang Semiarti (The East Java Biological Society, 2007)
Research of the structure and development pattern of somatic embryos from callus of leaf explants moon orchid Phalaenopsis amabilis (L) Bl had been done. One year old of plantlets were used as explants sources. Basal leaf of these explants were cultured in Somatic Embryo Induction Medium (SEIM) e.i.: NP(New Phalaenopsis) medium added with 2 mg/L NAA, 1 mg/L BA, 10 g/L sucrose, and 2 g/L gellan gum. Then somatic embryos were transferred to EMM (Embryo Maturation Medium) e.i.: NP medium added with 1 mg/L NAA, 1 mg/L BA, 10 g/L sucrose, and 2 g/L gellan gum. Finally, mature somatic embryo were transferred to NP medium without plant growth regulator as Embryo Germination Medium (EGM). The origin of somatic embryos initially from single cell at the pheriphery of embryogenic callus. These cells then devided in mitotic repeatedly formed globular proembryo, elongation embryo, and completed embryo. The structure and development pattern of somatic embryos as the same as with zygotic embryo.